2019
DOI: 10.1007/s00253-018-09594-x
|View full text |Cite
|
Sign up to set email alerts
|

Tremorgenic and neurotoxic paspaline-derived indole-diterpenes: biosynthetic diversity, threats and applications

Abstract: Indole-diterpenes (IDTs) such as the aflatrems, janthitrems, lolitrems, paspalitrems, penitrems, shearinines, sulpinines, and terpendoles are biogenetically related but structurally varied tremorgenic and neurotoxic mycotoxins produced by fungi. All these metabolites derive from the biosynthetic intermediate paspaline, a frequently occurring IDT on its own right. In this comprehensive review, we highlight the similarities and differences of the IDT biosynthetic pathways that lead to the generation of the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 174 publications
(310 reference statements)
0
30
0
1
Order By: Relevance
“…In this study, we demonstrated that targeted disruption of the idtP and idtF genes in C. paspali modulates the IDT product spectrum towards paspaline-type IDTs such as paspaline (1) and paspalinine (3). These results highlight the metabolic engineering potential of the A. tumefaciens-mediated C. paspali transformation system (Kozák et al 2018) in creating efficient platforms for the production of the IDT nucleus for combinatorial biosynthesis and the large-scale production of complex IDTs for various biomedical applications in the future (Kozák et al 2019).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In this study, we demonstrated that targeted disruption of the idtP and idtF genes in C. paspali modulates the IDT product spectrum towards paspaline-type IDTs such as paspaline (1) and paspalinine (3). These results highlight the metabolic engineering potential of the A. tumefaciens-mediated C. paspali transformation system (Kozák et al 2018) in creating efficient platforms for the production of the IDT nucleus for combinatorial biosynthesis and the large-scale production of complex IDTs for various biomedical applications in the future (Kozák et al 2019).…”
Section: Discussionmentioning
confidence: 71%
“…Paspalitrems are derived from paspaline (1, Fig. 1), the simplest cyclic IDT that contains a tetracyclic diterpene moiety fused with an indole group (Kozák et al 2019). The cyclic diterpene of paspaline is derived from geranylgeranyl diphosphate, while the indole originates from tryptophan via indole-3-glycerol phosphate (Liu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspergillus flavus IDTs belong to the group of tremorgenic mycotoxins that cause a special type of neurotoxicosis characterized by mental confusion, tremors, ataxia, seizures, hyperesthesia, nystagmus, diarrhea, and vomiting. This group of metabolites has been implicated as etiological agents of a neurologic disorder of livestock recognized as “staggers syndrome,” which involves muscle tremors and general excitability, posing a serious health threat for both cattle and humans (reviewed in Kozák, Szilágyi, Tóth, Pócsi, & Molnár, 2019; Reddy et al., 2019). IDT exposure in animal models has been associated with a significant loss of hippocampal nerve terminals that is manifested with synaptic perturbation of the amino acid neurotransmitters, GABA and glutamate.…”
Section: Aspergillus Flavus Linkmentioning
confidence: 99%
“…Neurological signs associated with ryegrass staggers disease has been reported in animals, particularly sheep, grazing on perennial ryegrass in Australia, New Zealand, as well as Pacific northwest of USA and Europe [13,14]. This imposes a negative impact on industry, particularly dairy, meat, and wool production involving grazing animals [15]. Thus, forage improvement programs have been involved in selecting novel endophytes that do not produce the known toxins; however, complex mixtures of the intermediate compounds are still present in marketed forage grasses.…”
Section: Introductionmentioning
confidence: 99%